MECHANISMS OF THE CULTURAL TRANSFER IN TRANSLATION - Gasparyan, Luiza (Armenian Folia Anglistika, 2023)
The article is the first attempt to reveal the mechanisms of “the cultural transfer” (the notion was first introduced by the French theorist M. Espagne) of the Armenian and Russian translations of Charles Dickens’s novels. Evidently, the Armenian translations of the novels were transferred and interpreted especially from the beginning of the 1880s, in Shushi (1890-91), Tiflis (different publications in the 1890s), Constantinople (1928), Baku (1898), Athens (1928), Cairo (1892), etc. The Armenian versions of Dickens’s creativity were either paraphrased or translated from the original language or from Russian as an intermediary language. The article outlines theoretical and practical issues related to the specifics of the artistic translation through the paradigm of cultural transfer. Being at the crossroads of West and East the Armenian national culture is characterized as a unique manifestation of cultural transmission and a pivotal basis of socio-cultural and geopolitical usus. The article sketches the situation of “cultural transfer” of Charles Dickens’s novels whose literary reputation was established in the Russian literary field, that consequently made an influence on Eastern Armenia.